Burn this house the making and unmaking of Yugoslavia (Duke Univ. Press, 1997)
Burn This House is the first book in English to represent the critical, nonnationalist voices inside the former Yugoslavia. Written primarily by Muslim, Croatian, and Serbian journalists and historians, this collection relies on the perspective of the people who live there to portray the chain of events that has led to the current genocidal wars in the heart of Europe. These essays elucidate the Balkan tragedy while directing attention toward the antiwar movement and the work of the independent media that has been largely ignored by the U.S. press. They show that, contrary to descriptions by the Western media, the roots of the warring lie not in ancient Balkan hatreds but rather in a specific set of sociopolitical circumstances that occurred after the death of Tito and culminated at the end of the Cold War.